Circuits and Synapses: Hypothesis, Observation, Controversy and Serendipity – An Opinion Piece - Thomson, Alex M. (Frontiers in Neural Circuits, 2021)
More than a century of dedicated research has resulted in what we now know, and what we think we know, about synapses and neural circuits. This piece asks to what extent some of the major advances - both theoretical and practical - have resulted from carefully considered theory, or experimental design: endeavours that aim to address a question, or to refute an existing hypothesis. It also, however, addresses the important part that serendipity and chance have played. There are cases where hypothesis driven research has resulted in important progress. There are also examples where a hypothesis, a model, or even an experimental approach - particularly one that seems to provide welcome simplification - has become so popular that it becomes dogma and stifles advance in other directions. The nervous system rejoices in complexity, which should neither be ignored, nor run from. The emergence of testable ‘rules’ that can simplify our understanding of neuronal circuits has required the collection of large amounts of data that were difficult to obtain. And although those collecting these data have been criticized for not advancing hypotheses while they were ‘collecting butterflies’, the beauty of the butterflies always enticed us towards further exploration.